Prediction of the Opsen PKB otential in East Java - Galuh Fitria RAMADHANI; Ayu Fury PUSPITA (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:Opsen PKB, as the latest additional tax levy imposed on taxpayers, needs to be studied to predict its revenue potential in order to support maximum tax realization. Methodology:Therefore, this study was written with the aim of predicting the potential of Opsen PKB in East Java using time series analysis via two scientific methods, namely simple linear regression and single exponential smoothing. The use of two different scientific methods for prediction is done to provide two different views on it.Findings:The results of the prediction calculation using simple linear regression showed good forecast accuracy and a steady increase in Opsen PKB. However, the prediction results were linearly patterned for the next ten periods, indicating that the model was not able to capture fluctuations in the time series data.Implication:Meanwhile, the results of calculations using one of the single exponential smoothing models predicted a decline for the next period, with no pattern.